GLOBALISAI MELAYU: Peluang dan Tantangan Membangun Identitas Melayu dalam Konteks Modernitas - Ihsan Sanusi (Tarbawiyah Jurnal Ilmiah Pendidikan, 2017)
This article discusses Malay globalization. Actually, what the Malays call is not an ethnic or ethnic community as many people today understand. It is time for Malays to collectively refine their view of Malay by building a different paradigm in a horizontal level through a not-cramped perspective of lokaism, since Malay is something that is not single (heterogeneous). In the identification and revitalization of Malay it is actually needed support from various components, both intellectuals and experts, as well as the holders and policy makers in several Malay rural countries. Thus expected the birth of a kind of strategic alliance between Malays in order to develop science and technology, politics, economics, culture, education and others. In any case, in the context of the modernity of Malay civilization that has found its identity will become more advanced as well as will be able to influence the great civilization of the world-if it can reverse the state of the hegemony into a hegemonizing culture.